Penentuan Nilai Sun Protection Factor secara In Vitro pada Ekstrak Etanol Akar Kalakai (Stenochlaena palustris Bedd) dengan Metode Spektrofotometer UV-Vis - Rabiatul Adawiyah (Jurnal Surya Medika (JSM), 2019)
The sunscreens or Sun Protecting Agent is the materials protecting the skin from the exposure to ultraviolet (UV) rays. Amount of Sun Protection Factor shows how many times the subject skin protection can be multiplied under the sun rays without erythema occurs. Kalakai contains some bio-active substance like phenol, flavonoid, alkaloid and terpenoid family which are proven as a very effective antioxidant. The purpose of this research was to determine the concentration of ethanol extract of kalakai root which has the potential as a sunscreen based on the Sun Protection Factor (SPF) parameter. Determination of SPF amount was carried out in vitro by UV-VIS spectrophotometer at a concentration of 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, and 350 ppm with a wavelength of 290-320 nm. The result showed that kalakai root ethanol extract indicated potential as a sunscreen at a concentration of 300 ppm and 350 ppm obtained SPF values respectively 11 and 14 classified as sunscreens with extreme ability levels.